Release system capable of degrading vena cava filter - XU HAO; GAO ZHIKANG (2014)
The utility model discloses a release system capable of degrading a vena cava filter, and the system comprises a filter, a release sheath (5), and a push sheath (6), wherein the filter, the release sheath (5) and the push sheath (6) are sequentially connected. The push sheath (6) consists of an outer casing pipe (61), a torsion controller (62), and a push guide wire (63). The system is characterized in that the filter consists of vertical columns (1), fixing anchors (2) and filtering bodies (3), and is in a lantern structure; the number of the vertical columns (1) is six, and two ends of each column (1) are separated and fused with the adjacent vertical columns (1); the heads of the vertical columns (1) are gathered to form a body, thereby forming six rhombic filtering bodies (3); the heads of the six rhombic filtering bodies (3) are fused; the peripheries of the six rhombic filtering bodies (3) are provided with the fixing anchors (2); the filter is made of degradable materials; the system provided by the utility model effectively prevents thrombus from entering into a pulmonary artery, is easy to implant into a vena cava, is accurate and stable in positioning, is not easy to damage a blood vessel, can be completely degraded in a human body after treatment, and avoids the risks caused by a conventional perpetual filter or a temporary filter.